2008
DOI: 10.3748/wjg.14.2200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estradiol and progesterone on the proinflammatory cytokine production by mononuclear cells from patients with chronic hepatitis C

Abstract: These findings suggest that E2 may play a favorable role in the course of persistent liver injury by preventing the accumulation of monocytes-macrophages and by inhibiting proinflammatory cytokine production, whereas progesterone may counteract the favorable E2 effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 30 publications
0
26
0
1
Order By: Relevance
“…Yet, estradiol and progesterone can have either immunostimulant or immunosuppressive effects (6,7,21,37,47). Possible explanations for the observed differences include factors such as the concentration, timing and duration of hormone treatment, and expression of specific receptor subtypes and receptor coactivators in distinct cell types of different species (2,6,13,38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, estradiol and progesterone can have either immunostimulant or immunosuppressive effects (6,7,21,37,47). Possible explanations for the observed differences include factors such as the concentration, timing and duration of hormone treatment, and expression of specific receptor subtypes and receptor coactivators in distinct cell types of different species (2,6,13,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…After birth, estradiol and progesterone blood levels decrease within less than 1 week to 0.1 nM and 5 nM, respectively, which corresponds to levels observed in adult males. Whereas estradiol has been shown to inhibit cytokine production by adult PBMCs, the effect of progesterone on adult immune cells is less clear (3,13,47). To evaluate the developmental response of immune cells to steroids, PBMCs from adult males and premenopausal females were preincubated for 16 h with estradiol (10 Ϫ7 to 10 Ϫ9 M) or progesterone (10 Ϫ5 to 10 Ϫ7 M) prior to stimulation with E. coli ( Fig.…”
Section: Estradiol and Progesterone Inhibit Cytokine Production Bymentioning
confidence: 99%
“…For instance, an in vivo study showed that transdermal estrogen therapy reduces circulating levels of several cytokines, including MCP-1 (Yasui et al 2009). In parallel, studies in vitro demonstrate that estrogen reduces MCP-1 production in several cells, such as peripheral blood mononuclear cells and immature dendritic cells (Bengtsson et al 2004, Yuan et al 2008). The present study provides the first evidence that estrogen directly acts on VSMCs by decreasing LPS-stimulated MCP-1 production, which adds new insight into estrogen's anti-inflammatory functions in cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse peritoneal macrophages express receptors for both estradiol (both the alpha and beta isoforms) and progesterone (Huang et al, 2008), and are responsive to these hormones in vitro. Progesterone promotes the expression of proinflammatory cytokines, including tumour necrosis factor alpha (TNF), CCL2 (also known as monocyte chemoattractant protein 1) and interleukin 1 beta (IL1), by mouse and human macrophages, whereas estradiol suppresses expression (FrazierJessen and Kovacs, 1995;Huang et al, 2008;Yuan et al, 2008). Alternatively, indirect hormonal regulation might be mediated by the epithelium.…”
Section: Hormonal Regulation Of Macrophage Functionmentioning
confidence: 99%